2012
DOI: 10.3390/ijerph9051566
|View full text |Cite
|
Sign up to set email alerts
|

“It Is Good for My Family’s Health and Cooks Food in a Way That My Heart Loves”: Qualitative Findings and Implications for Scaling Up an Improved Cookstove Project in Rural Kenya

Abstract: The use of indoor, three-stone fire pits in resource–poor countries is a substantial burden on human health and the environment. We conducted a pilot intervention promoting the purchase and use of an improved cookstove in rural Kenya. The goals of this qualitative inquiry were to understand the motivation to purchase and use; perceived benefits and challenges of cookstove use; and the most influential promotion activities for scaling up future cookstove promotion. Purposive sampling was used to recruit 10 cook… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
69
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(75 citation statements)
references
References 25 publications
6
69
0
Order By: Relevance
“…Time savings associated with cooking on multiple pot-holes, were considered an important advantage [18,31,32,34,36,40]. …”
Section: Resultsmentioning
confidence: 99%
“…Time savings associated with cooking on multiple pot-holes, were considered an important advantage [18,31,32,34,36,40]. …”
Section: Resultsmentioning
confidence: 99%
“…A qualitative study of the same villages found that upesi jiko users reported a noticeable reduction in visible smoke in their homes compared with 3-stone firepits. 10 Upesi jikos reportedly burned fuel more efficiently and cooked food faster than 3-stone firepits, which may have decreased exposure to smoke in the home. 9 Chemicals in wood smoke provoke inflammatory responses in the lungs, irritate airways, and suppress the immune system.…”
Section: Discussionmentioning
confidence: 99%
“…Reduction of exposure to important pollutants, like smoke from cooking fires inside the home [46], is being addressed through research studies supported by the Global Alliance for Clean Cookstoves, including in western Kenya [54], [55]. The age of death for some neoplasms, such as female breast cancers, is young; in our study population women died at a median age of 41y (IQR 31–47), with 85% of deaths reported among females <65y.…”
Section: Discussionmentioning
confidence: 99%